Media Pembelajaran Bahasa Arab Berbasis E-Learning - Huda, Khoirul; Wulandari, Nawang (Department of Arabic Education - Faculty of Educational Sciences, 2022)
The e-Learning medium is a learning process in which the learning participants are separated from the teacher. There is also the use of electronic technology as a learning medium. The Arabic Online Program is an e-Learning-based Arabic language learning media for foreign speakers. Saudi Electronic University initiated this virtual Arabic learning program. Arabic-Online will enable non-native Arabic speakers to learn the language of the world. This website will also provide learning Arabic as a communication tool, which will include vocabulary as well as language skills.